Taxonomic review of the genus Thalpomena Saussure, 1884 with new synonyms - Dey, Lara-Sophie; Hochkirch, Axel; Moussi, Abdelhamid; Seidel, Matthias; Husemann, Martin (Zootaxa, 2022)
The genus Thalpomena Saussure, 1884 is distributed in North Africa, Somalia and Ethiopia. It currently contains nine species, including one species with four subspecies; Seven of them (including one with four subspecies) are distributed in the Atlas Mountains, one in Libya and one (originally described in the genus Vosseleria) in the Somali Highlands. In this study, we propose taxonomic changes based on morphological, genetic, ecological and morphometric data from a previous study. The following species remain valid: Thalpomena algeriana (Lucas, 1849); Thalpomena azureipennis Uvarov, 1927; Thalpomena coerulescens Uvarov, 1923; Thalpomena dernensis (Werner, 1908); and Thalpomena viridipennis Uvarov, 1927. The following names are proposed here as junior synonyms of T. algeriana: Thalpomena algeriana intermedia Dirsh, 1949 (new synonym), Thalpomena algeriana montana Dirsh, 1949 (new synonym), Thalpomena coeruleipennis Finot, 1895 (new synonym), Thalpomena deserta Dirsh, 1949 (new synonym). Thalpomena rungsi Dirsh, 1949 is a new synonym of T. azureipennis; Thalpomena algeriana maroccana Dirsh, 1949 is a new synonym of T. viridipennis. The only East African representative of the genus, Thalpomena schulthessi (Uvarov, 1923), is transferred to the genus Vosseleriana (new combination).